Thailand's upcoming challenge consolidating regional integration around the Bay of Bengal - Hussain, Nazia (2024)
Ahead of the 6th BIMSTEC Summit, Thailand, as Chair of BIMSTEC, is focused on furthering the regional organisation's institutionalisation and on strengthening connectivity among the member states around the Bay of Bengal.